MARKETING MIX EFFECT ON SALES VOLUME OF BANANA CHIPS IN JOINT BUSINESS GROUP (KUB) "TELO REZEKI" IN BANDAR LAMPUNG - Olivia Tjioener (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The study aims to examine and analyze the effect of the marketing mix on sales (studies in Business Group (KUB) "Telo Rezeki" n Bandar Lampung). The population used in this study amounted to 73 respondents, of the total consumer Business Group (KUB) "Telo Rezeki" In Bandar Lampung. Data analysis method used is multiple linear regression analysis. Based on the analysis, the regression equations obtained are as follows:Y = 2.117+0.288X1+0.174X2+0.150X3+0.327X4+0.138X5+0.518X6+0.579X7 + 1.803+ eThe results of the T test, product, process, price, promotion, place, people and physical products have significant positive effect on sales. The results simultaneously with the F test showed that all independent variables significantly influence sales. The coefficient of determination (R2) of 0679 which showed that 64.4% of sales variables can be explained by the independent variable product, process, price, promotion, place, people and physical products, while the rest of 35.6,% is explained by other variables.